Relationship Knowledge Of Maternal Contracting Techniques With The Incidence Of Perineal Rupter At Kapas Health Center - Umi Kalsum; Dwi Ghita (Lembaga Pengembangan Kinerja Dosen, 2022)
Childbirth is a series of processes that end with the expulsion of the products of conception by the mother. The World Health Organization (WHO) estimates that there are more than 585,000 maternal deaths caused by complications of pregnancy and childbirth worldwide every year. Of the many who go through labor, not all of them experience tearing of the birth canal or perineal rupture. 1 in 4 women who experience perineum intact during labor. Due to the birth process, the perineum is widened by 170% from the transverse position (side to side) and 40-6-% in the vertical position (front to back) during the crowing process, so that there is a greater risk of perineal rupture. In Indonesia, out of a total of 1951 vaginal births, 1465 or 75% experienced perineal rupture, 158 or 8% received perineal sutures due to episiotomy and 566 or 29% experienced spontaneous tears. The purpose of this study was to determine the relationship between the technique of straining in childbirth and the incidence of perineal rupture at the Kapasa Health Center The research method used was an analytic survey, using the Cross Sectional Study approach, which is a form of observational (non-experimental) study to find the relationship between the independent variable and the dependent variable by taking momentary measurements in the research conducted by analyzing the relationship between knowledge of Maternity Straining Techniques and Events Perineal Rupture at the Kapasa Health Center. The results showed that the level of knowledge was not good with the incidence of perineal rupture as many as 11 respondents (52.3%) and knowledge.